2016
DOI: 10.1007/s40870-016-0071-5
|View full text |Cite|
|
Sign up to set email alerts
|

Shock Response of Polymethylmethacrylate

Abstract: Polymethylmethacrylate (PMMA) from two suppliers is subjected to shock loading up to 2 GPa to develop understanding of the effect of manufacturing process on the shock response. The particle velocity, shock velocity, and longitudinal and lateral stresses are measured simultaneously and independently using photon Doppler velocimetry and manganin gauges. The particle velocity measurements agree with data in the literature. The calculated shear stress was seen to deviate from linear behavior at approximately 2 GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Values of C and S for the CS materials, PMMA, and glass for different velocity ranges (Ahrens and Johnson ; Jordan et al. ).…”
mentioning
confidence: 99%
“…Values of C and S for the CS materials, PMMA, and glass for different velocity ranges (Ahrens and Johnson ; Jordan et al. ).…”
mentioning
confidence: 99%
“…As a consequence, we have taken the opportunity to study the purely mechanical response of two of these materials (the HMX based PBXs EDC32 and EDC37), using manganin stress gauges in longitudinal and lateral orientation to the shock loading axis. This technique has been used previously on metals [43,44], ceramics and silicate glasses [45,46], polymers [47,48] and particulate composites [24]. The primary goal of this investigation is to determine the shear strength of these materials, both as a function of imposed shock stress and its variation with time behind the shock front.…”
Section: Discussionmentioning
confidence: 99%
“…They found that wave propagation was affected by nonlinearity in the material, strain-rate dependence, and elastic-plastic effects. More recent experimentation by Jordan et al [32] confirmed and expanded upon their findings. Carter and…”
Section: Polymersmentioning
confidence: 70%
“…The results from each experiment will now be discussed on a material-by-material basis in the following sections of this report. [32]. c N.S.…”
Section: Signal Processingmentioning
confidence: 99%
See 1 more Smart Citation